Case Report: Diagnosis and treatment of equine ascending placentitis: compilation of 17 case reports - Hemberg, Elisabeth; Morrell, Jane M. (Frontiers in Veterinary Science, 2025)
Placentitis (inflammation of the placenta) most commonly occurs during the last trimester of pregnancy, frequently due to bacterial entry via the vulva. The outcome of the pregnancy, i.e., prevention of abortion or the birth of a compromised foal, depends on when treatment is initiated, the appropriate medication, and surgical correction of the vulva to ensure an effective seal. In this study, during the period 2012–2024, 17 mares were referred to the clinic, presenting with signs of placentitis, most commonly premature udder activity and/or discharge from the vulva. All mares maintained the pregnancy after treatment, ultimately producing live foals that survived. The earliest cases involved mares with the most pronounced clinical signs; these mares received treatment with poor perfusion into the placenta and delivered septicaemic foals. The remaining foals born exhibited only minor clinical signs or appeared healthy. For later cases, treatment with drugs providing good uterine perfusion continued until foaling, including trimethoprim sulphate twice a day and acetylsalicylic acid, a COX-1 anti-inflammatory drug, administered twice a day until parturition, if necessary. In addition, for 16 mares, a vulvoplasty (Caslick’s operation) was performed, or was extended if the mare had already undergone surgery.